Konsepsi Hak Asasi Manusia dan Implementasinya di Indonesia - Bambang Sutiyoso (Universitas Islam Indonesia, 2002)
The issues of human rights constitute the global issues recently that will not ignore with some reasons including in Indonesia. The concept of human rights and its realization in each state may not similar although actually the substance of human rights is equal. In this respect there are three concepts and implementations of human right in the world that be regarded as the representatives of western states, Socialism-communism and Islamic doctrine. The consequence of human rights emerges human obligations, that both human rights and human obligations are parallel and a system. The ignoring one of them will raise heavy infraction of human rights itself. The Implementation of human rights in Indonesia particularly even though many cases emerge generally either development or the maintenance ofhuman rights seems the progress. In this sense, the regulating law of human rights by legislating the rules and by establishing the Human Rights Court in overcoming many cases of heavy evading of raised human rights.